Monitoring the CO2 Emission Trajectory and Reduction Effects by ETS and Its Market Performances for Pre- and Post-pandemic China - Luo, Kun; Xu, Aidi; Ye, Rendao; Li, Wenqian (Frontiers in Public Health, 2022)
The Covid-19 pandemic has caused great shocks on economic activities and carbon emissions. This paper aims to monitor the CO2 emission trajectory in China before and after the pandemic outbreak, and analyze the emission reduction effects by ETS and its market performances, which are important determinants underlying the trajectory and key drivers for emission reductions. We firstly find out a rather consistent trajectory of CO2 emissions in pre- and post-pandemic China over a two-year time horizon, using the near-real-time datasets of daily CO2 emissions by Carbon Monitor and applying the Cox-Stuart trend test and mean equality test. We then examine the emission reduction effects by China’s carbon ETS and its pilot market performances, using the methodologies of DID and PSM-DID as well as pre-pandemic region-level emission datasets by CEADs. Furthermore, it’s found that the ETS pilot markets, which are immature with defects, have been performing more vulnerably in terms of liquidity and transaction continuity under pandemic shocks, thus undermining the emission reduction effects by ETS. These findings are providing insights into further mechanism design of the carbon ETS to the end of steady emission reductions even under shocks for post-pandemic China. It’s of particular importance now that the nationwide market has been launched and needs to be enhanced based on lessons learned.